Room temperature ionic liquid electrolytes for redox flow batteries - Ejigu, Andinet; Greatorex-Davies, Peter; Walsh, Darren A. (Elsevier, 2015)
Redox flow batteries (RFBs) usually contain aqueous or organic electrolytes. The aim of this communication is to explore the suitability of room temperature ionic liquids (RTILs) as solvents for RFBs containing metal complexes. Towards this aim, the electrochemistry of the metal acetylacetonate (acac) complexes Mn(acac)3, Cr(acac)3, and V(acac)3 was studied in imidazolium-based RTILs. The V2+/V3+, V3+/V4+, and V4+/V5+ redox couples are quasi-reversible in 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, [C2C1Im][N(Tf2)]. The Mn(acac)3 and Cr(acac)3 voltammetry, on the other hand, is irreversible in [C2C1Im][N(Tf2)] at glassy carbon (GC) but the rate of the Mn2+/Mn3+ reaction increases if Au electrodes are used. Charge–discharge measure- ments show that a coulombic efficiency of 72% is achievable using a V(acac)3/[C2C1Im][N(Tf2)]/GC cell.